Toward a global consensus on outcome measures for clinical trials in Tinnitus: report from the First International Meeting of the COMiT Initiative, November 14, 2014, Amsterdam, The Netherlands - Hall, Deborah A (2017)
In Europe alone, over 70 million people experience tinnitus; for seven million people, it creates a debilitating condition. Despite its enormous socioeconomic relevance, progress in successfully treating the condition is somewhat limited. The European Union has approved funding to create a pan-European tinnitus research collaboration network (2014-2018). The goal of one working group is to establish an international standard for outcome measurements in clinical trials of tinnitus. Importantly, this would enhance tinnitus research by informing sample-size calculations, enabling meta-analyses, and facilitating the identification of tinnitus subtypes, ultimately leading to improved treatments. The first meeting followed a workshop on ``Agreed Standards for Measurement: An International Perspective{''} with invited talks on clinimetrics and existing international initiatives to define core sets for outcome measurements in hearing loss (International classification of functioning, disability, and health core sets for hearing loss) and eczema (Harmonizing outcome measures for eczema). Both initiatives have taken an approach that clearly distinguishes the specification of what to measure from that of how to measure it. Meeting delegates agreed on taking a step-wise roadmap for which the first output would be a consensus on what outcome domains are essential for all trials. The working group seeks to embrace inclusivity and brings together clinicians, tinnitus researchers, experts on clinical research methodology, statisticians, and representatives of the health industry. People who experience tinnitus are another important participant group. This meeting report is a call to those stakeholders across the globe to actively participate in the initiative.}